OS 34-04 SAFETY OF EARLY INTENSIVE BLOOD PRESSURE LOWERING IN CEREBRAL SMALL VESSEL DISEASE AND CHRONIC KIDNEY DISEASE IN ACUTE INTRACEREBRAL HEMORRHAGE. (September 2016) - Anderson, Craig; Sato, Shoichiro; Delcourt, Candice; Arima, Hisatomi; Zhang, Shihong; Salman, Rustam RAl-Shahi; Stapf, Christian; Woo, Dan; Flaherty, Matthew; Vagal, Achala; Wang, Jiguang; Chalmers, John
Abstract : Objective: The INTERACT2 trial demonstrated beneficial effects of early intensive blood pressure (BP) lowering in intracerebral hemorrhage (ICH). However, concerns persist over harms associated with the treatment, particularly in patients with cerebral small vessel disease (CSVD) (ie white matter lesions [WML], lacunes and atrophy) and renal failure. We determined associations of CSVD, and renal failure, on outcomes in INTERACT2 participants. Design and Method: There were 2069/2839 patients with baseline brain CT (< 6hr ICH onset). WML grade (van Swieten scale), 2 linear measurements of brain atrophy (frontal ratio [FR] and third ventricle Sylvian fissure distance [TSD]), and the presence of lacunes were analyzed centrally by 3 independent neurologists blind to clinical data. Admission estimated glomerular filtration rate (eGFR) was categorized into 3 groups based on the CKDEC equation: normal or high (> 90 mL/min/1.73 m 2 ), mild (60–90 mL/min/1.73 m 2 ), and moderate-severe (< 60 mL/min/1.73 m 2 ) decrease. Results: WML and brain atrophy were associated with death/disability (mRS score 3–6) at 90 days: adjusted ORs for WML (grade 3 and 4 vs. 1), FR and TSD (most vs. least severe atrophy quartile) were 1.42 (95%CI 1.02–0.98), 1.47 (1.08–1.99) and 1.64 (1.21–2.22), respectively (P trend < 0.05). No significant differences in effects of intensive BP lowering in subgroups of CSVD. Of 2623 participants with renal data, 912 (35%) and 280 (11%) had mild and moderate-severe decreased eGFR. Compared to normal or high eGFR, patients with moderate-severe decrease in eGFR had the greatest risk of death or major disability at 90 days (adjusted odds ratio 1.82, 95% CI 1.28–2.61). The effects of early intensive BP lowering were consistent across different levels of eGFR (P = 0.5 for homogeneity). Conclusions: Patients with CSVD manifestations of WML and brain atrophy, and renal failure, have significantly worse outcome in acute ICH. However, intensive BP lowering provides similar treatment effects irrespective of degree of CSVD or renal failure.